A novel conditional anonymity scheme for vehicular communication networks. (29th September 2019) - Wang, Xiaoliang; Bai, Liang; Mausler, Brandon; Singh, Pitam
Summary: Vehicular communication networks are traffic applications of the Internet of Things consisting of vehicle nodes, roadside units, service providers, and other components. To protect the vehicle privacy, some vehicular communication networks adopt anonymous schemes. However, in these anonymous schemes, anonymity abuse is inevitable. In order to protect vehicular privacy and prevent anonymity abuse, some conditional anonymous authentication schemes based on cryptography have been proposed. However, most of these methods have complex computation and large communication overhead, which makes them difficult to meet the actual requirement of high‐speed traffic in vehicular communication networks. In this paper, a novel conditional anonymity scheme called VKPCA (vehicular communication network based on kernel principal component analysis [KPCA]) is proposed, which can protect vehicle privacy while avoid anonymity abuse. The simulation results show that this scheme has lower computational complexity and communication overhead than the conventional anonymous authentication scheme. Abstract : In this paper, a novel conditional anonymity scheme called VKPCA (vehicular communication network based on kernel principal component analysis [KPCA]) is proposed, which can protect vehicle privacy as well as avoid anonymity abuse. Unlike other pseudonym authentication systems based on cryptosystem, VKPCA uses the idea of feature dimensionality reduction to form the pseudonym of vehicles, which provides a lightweight pseudonym authentication scheme for vehicular communication networks.